Razonamiento lógico matemático en la enseñanza de la Matemática. - Rodríguez Arias, Ruddy Lorena (2023)
The present research started from the premise of determining the incidence of mathematical-logical reasoning in matematics teaching to students in the fifth year of basic education of the Educational Unit "Camilo Gallegos Domínguez" of Pastaza Province, Mera, Shell tonw, in that sense, in the first place, the diagnosis was made through a survey and an observation sheet allowing to collect information on the object of research with its two variables; This described the need to improve the development of logical-mathematical reasoning through a proposal focused on methodological strategy sessions, taking into account the needs of the students. Once the sessions were applied and the corresponding evaluation was made through a pretest and posttest, the results showed that 87.10% (27 students) achieved a significant improvement in the development of logical-mathematical reasoning and the learning of mathematics, compared to those who are in a moderate range with 12.90% (4 students), The results show that the proposal "Guide of techniques for the development of logical-mathematical reasoning in the process of teaching mathematics to students in the fifth year of basic education at "Camilo Gallegos Domínguez" Educational Unit contributed significantly to the process of teaching mathematics, therefore it is considered that the application and continuity of this instrument is feasible.